Study of the nutritional status and some selected factors affecting the nutritional status of children of age 1-5 years in a fishing community in DDHS area Ambalangoda - Chandrasekara, K.P.S.D.S (My University, 2003)
Descriptive cross sectional study was carried out to asses the nutritional status and some selected factors affecting it among children of 1-5 years of fishing families residing in the DDHS area Ambalangoda. the study revealed that the prevalence of underweight was 31 while stunting and wasting were 23 and 11.3 respectively. Ability of father to read and understand a written documents was found to be significantly associated with stunting. Mother's ability to read and understand written documents was found to be significantly associated with underweight and wasting. Father's habit of smoking was significantly associated with underweight and stunting of children, while his alcohol consumption was significantly related to children being underweight, stunting and wasting. Frequent quarrels and family disputes were associated with all three forms of under nutrition; stunting, wasting and underweight at a higher level of significant. Method of disposal of child excreta was also associated with underweight of children significantly. More than one third of the population was suffering from upper respiratory tract infections during preceding three weeks of the study. Males were found to be more undernourished than females. No significant association was found existing between the level of education of parents and the nutritional status of children